2021
DOI: 10.3390/foods10010181
|View full text |Cite
|
Sign up to set email alerts
|

Freshness Quality and Shelf Life Evaluation of the Seaweed Ulva rigida through Physical, Chemical, Microbiological, and Sensory Methods

Abstract: In Europe, the consumption of seaweeds and derived products has increased in recent years, due to the expansion of Asian cuisine and the emergence of many top-level chefs. Often in collaboration with scientists, many have initiated a new gastronomy using algae. However, little is known about the quality and degree of freshness of seaweeds for direct consumption or fresh use. For this reason, different analytical methods were applied to test sea vegetables and other marine products. These methods included physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Salinity was measured by using a salinity refractometer for seawater and marine aquaria 0–10% hydrometer with automatic temperature compensation RHS-MR110 ATC ( 45 ). The texture was measured with a digital texturometer (model 53205, TRTuroni, Srl Forlì, Italy) on JF umbrellas ( 46 , 47 ). A penetration test was performed using a three-bars probe (3 × 22 mm) for a total plunger area of 1.98 cm 2 by operating on samples consisting of radial triangular slices of the JF umbrella.…”
Section: Methodsmentioning
confidence: 99%
“…Salinity was measured by using a salinity refractometer for seawater and marine aquaria 0–10% hydrometer with automatic temperature compensation RHS-MR110 ATC ( 45 ). The texture was measured with a digital texturometer (model 53205, TRTuroni, Srl Forlì, Italy) on JF umbrellas ( 46 , 47 ). A penetration test was performed using a three-bars probe (3 × 22 mm) for a total plunger area of 1.98 cm 2 by operating on samples consisting of radial triangular slices of the JF umbrella.…”
Section: Methodsmentioning
confidence: 99%
“…The initial TVC counts were 3.2 and 5.2 log CFU/g in 2020 and 2019 samples, respectively, while microorganisms reached the level of 7.0 log CFU/g on days 2 and 4 at 5 °C in 2019 and 2020 samples, respectively. Previous studies have also reported 7.0–8.0 log CFU/g as the threshold level for the onset of deterioration in marine algae [ 19 , 20 ]. For the 2019 samples, Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors affect this population range, including species differentiation, location, environmental conditions and seasonal differentiation, as well as the seaweed life cycle and the fact that different bacterial communities are present on different parts of the seaweed thallus [ 15 , 20 ]. Seaweed quality assessment is the main focus of recent studies, as various factors including chemical, enzymatic and microbiological alterations contribute to the quality degradation of these products [ 19 ]. Although there are few studies investigating the microbial diversity of marine algae, and even fewer estimating the microbial growth and the shelf life of different seaweed species, almost none have focused on the spoilage potential of the identified microorganisms and the type of deterioration they cause.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximity of farmed material to processing location is also a strong consideration, as harvested macroalgae is subject to rapid microbial degradation [22] and composition losses, e.g., carbohydrate and polyphenol losses in kelps [23]. If no steps are taken to stabilise fresh macroalgae, microbiological counts of spoilage bacteria (aerobic colony count) very rapidly exceed the upper limit of determination, and yeasts and moulds start to be problematic [24]. Unpublished industry-led studies [25] have shown that microbial degradation is critically dependent on both seawater temperature and storage temperature after harvest.…”
Section: Supply Chainmentioning
confidence: 99%